Applying the Voltammetry of Microparticles to Assess the Metal Ion Excess Following a Precipitation Reaction: The Determination of Arsenic - Paez-Collio, M; Paez-Collio, M; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Espinoza-Vergara, J; Espinoza-Vergara, J (Springer, 2019)
Here we demonstrate that the metal ion excess after precipitating a sparingly soluble metal salt can be conveniently determined by a secondary precipitation of a metal salt on an electrode surface, followed by measuring the solid-state electrochemical response of that salt. As an example, the analysis of the arsenic content of solutions is presented. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.